MORTE NA PERSPECTIVA DO PACIENTE E FAMÍLIA NA UNIDADE DE TERAPIA INTENSIVA - Cavalcanti, Alessandra do Nascimento (2018)
The intensive care unit is an environment that directs your care to critically ill patients, has in its statistical numbers high incidence of deaths. The patient and family are public who deserve to be analyzing from a rough experience of finitude. The objective of this article is doing review in the literature publications of death in ICUs from the perspective of patients and families. A scan of articles occurred through Systematic Review with demarcation descriptors 'Psychology' AND 'Death' AND 'intensive care unit', and inclusion criteria for analysis of articles consistent. The articles were divided into five thematic categories (The death from the patient's perspective; The death from the perspective of the family; Communication of bad news; Care end of life; religiosity and death) to facilitate the exploitation of the contents of the articles. The need for integration of care focused on the family and patients. Consider possibilities of new studies related to innovative practices and care about the flexibility of spaces for debate between patients and families about death.